Ensino de cinemática por investigação usando robótica - NUNES, Joicy Beatriz de Souza (2024)
This work resulted from a project developed in the Institutional Program of Extension Scholarships (PIBEX) at UFPA, Salinópolis campus. Within the field of Physics education, there exists a rich repertoire of technical terms that must be employed, posing a challenge to students' comprehension and interest. It is the responsibility of educators to facilitate the teaching-learning process by incorporating new methodologies. To contribute to this demand, an Inquiry Teaching Sequence was developed, utilizing an experimental Arduino prototype, adopting inquiry-based teaching as a didactic approach that enables planning, questioning, and knowledge construction. The inquiry activity was conducted with first-year high school students from public schools in Salinópolis, aiming to analyze how inquiry activities, using robotics as instructional material, contribute to the development of meaningful learning. The activity facilitated scientific literacy in the field of kinematics, with a focus on Uniform Linear Motion